A Need of Agricultural Students at King Mongkuts Institute of Technology Ladkrabang for Developing u-Learning based on Flipped Classroom Concept - Kulachai Kultawanich; Nutthakorn Songkram (My University, 2018)
Ubiquitous learning (u-Learning) has become the replacement of e-Learning.Since the mobile devices become a part of student's life.A lot of attention is drawn to u-Learning, which allow students access to the learning environment from any device platform.This paper aims to assess the needs of Agricultural students toward the u-Learning Model based on flipped classroom concept and studying the feasibility of the u-Learning model.This research is based on a survey developed on a sample of 274 students from 3 department in the faculty of Agricultural technology, King Mongkut's Institute of Technology Ladkrabang (KMITL).The relevant results of the study show that: the most of participants preferred to use mobile and laptop more than PC and tablet, while the flipped classroom pedagogy was suitable for the students.
Keywords: Flipped Classroom; Technology-Enhanced Education Studies